2022
DOI: 10.1093/jcag/gwac018
|View full text |Cite
|
Sign up to set email alerts
|

Financial Conflicts of Interest in Propensity Score-Matched Studies Evaluating Biologics and Biosimilars for Inflammatory Bowel Disease

Abstract: Background Propensity score matching (PSM), a statistical technique that estimates a treatment effect by accounting for predictor covariates, has been used to evaluate biologics for inflammatory bowel disease (IBD). Financial conflicts of interest are prevalent in the marketing of biologic medications. It is unclear whether this burden of conflicts is present among authors of PSM studies comparing IBD biologics and biosimilars. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The burden of inaccurate COI disclosure in medicine has been reported using the OPD across various specialties ranging from robotics, orthopedics, gastroenterology, and ophthalmology to occupational health research. 3,5,[18][19][20] Hsieh et al 21 reported that nearly 97% of the authors of 100 US-based top-cited image-guided procedure publications failed to accurately disclose their COI. Inaccurate COI disclosures are highly common even among high-impact journals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The burden of inaccurate COI disclosure in medicine has been reported using the OPD across various specialties ranging from robotics, orthopedics, gastroenterology, and ophthalmology to occupational health research. 3,5,[18][19][20] Hsieh et al 21 reported that nearly 97% of the authors of 100 US-based top-cited image-guided procedure publications failed to accurately disclose their COI. Inaccurate COI disclosures are highly common even among high-impact journals.…”
Section: Discussionmentioning
confidence: 99%
“…These physician-industry relationships are important for technological advancement; however, these ties introduce a potential source of bias that may influence research findings. Studies have shown that physician researchers who receive payments from industries are more likely to demonstrate results favorable to the funding companies and prescribe drugs and devices produced by these companies 4,5 . They may also unduly influence other physicians by contributing to articles that other providers use to guide their own clinical practice 6,7 …”
mentioning
confidence: 99%
See 1 more Smart Citation